2019
DOI: 10.22454/fammed.2019.232634
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Oral Health Training for Primary Care Clinicians: A Systematic Review

Abstract: Background and Objectives: Despite recent improvements in access to health care, many Americans still lack access to dental care. There has been a national focus on interprofessional education and team-based care to work toward the integration of services including dental care into primary care. The purpose of this systematic review is to understand the impact of implementing oral health curricula in primary care training on measurable changes in primary care practice. Methods: Researchers utilized a two-step … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…When compared pre-vs. post-test scores, students showed significant improvement in knowledge [mean (SD) = 6.57 (1.74) vs. 8.76 (1.33), t = −7.71, p < 0.001], confidence [mean (SD) = 8.00 (5.99) vs. 16.46 (3.33), t = −10.30, p = <0.001] and attitude [mean (SD) = 6.52 (1.79) vs. 7.52 (1.04), t = −4.24, p = <0.001] (Table 5). 3.4.…”
Section: Knowledge Confidence and Attitudementioning
confidence: 99%
See 1 more Smart Citation
“…When compared pre-vs. post-test scores, students showed significant improvement in knowledge [mean (SD) = 6.57 (1.74) vs. 8.76 (1.33), t = −7.71, p < 0.001], confidence [mean (SD) = 8.00 (5.99) vs. 16.46 (3.33), t = −10.30, p = <0.001] and attitude [mean (SD) = 6.52 (1.79) vs. 7.52 (1.04), t = −4.24, p = <0.001] (Table 5). 3.4.…”
Section: Knowledge Confidence and Attitudementioning
confidence: 99%
“…With appropriate training, primary care providers could be effective partners in preventing and reducing oral health problems in children [15]. An interdisciplinary oral health education program has proven effective in training primary care students to adopt oral health assessments into their practice [16]. Post-training surveys show students improved significantly in their oral health knowledge, confidence in giving oral health counseling, and attitudes in including oral health examination into their practice.…”
Section: Introductionmentioning
confidence: 99%
“…When searching across all of PubMed for articles with "scoping" in the title, one can see the exponential growth in the number of hitsmore than 1,600 publications in 2019. Yet, a simple PubMed search for "scoping" (in title or abstract) identified only one study previously published in Family Medicine, 4 and none published in Annals of Family Medicine. In family medicine, perhaps more than any other discipline, we understand the value of taking a broad perspective, so we should do more of this work.…”
mentioning
confidence: 99%
“…Multiple additional organizations, including the Association of American Medical Colleges (AAMC) 12 and the Society of Teachers of Family Medicine (STFM), 13 have recognized the importance of including oral health in primary care training and have developed programs or instituted training requirements to address this need 14 . A recent systematic review, however, found that implementation of such programs has been sporadic, and evaluation of them has been rare 15 …”
mentioning
confidence: 99%
“…14 A recent systematic review, however, found that implementation of such programs has been sporadic, and evaluation of them has been rare. 15 The National Interprofessional Initiative on Oral Health (NIIOH) is a coordinated effort to improve oral health training for clinicians providing primary care in the fields of nursing, advanced practice nursing, physician assisting, and medicine. Through the initiative's nursing arm, Haber first advocated across health professions for inclusion of the oral examination in the HEENT (head, ears, eyes, nose, and throat) exam, re-naming the acronym HEENOT, 16 and subsequently created the Oral Health Nursing Education and Practice (OHNEP) toolkit to further integrate efforts among primary care nurse practitioner (gerontology, family medicine, pediatric) and midwifery programs.…”
mentioning
confidence: 99%